Membangun Budaya Literasi Akademik: Sosialisasi Penulisan Karya Tulis Ilmiah bagi Siswa SMA Negeri 5 Bantaeng - Meliyana R, S.Pd, M.Si, Sitti Masyitah; Isma Muthahharah; Zakiyah Mar’ah; Muh. Isbar Pratama; Hardianti Hafid (Ininnawa : Jurnal Pengabdian Masyarakat, 2025)
Scientific writing skills are essential competencies that high school students must acquire as part of strengthening academic literacy. However, observations at SMA Negeri 5 Bantaeng revealed that most students lack a solid understanding of scientific writing concepts and techniques. This community service program aimed to provide socialization and training on scientific writing to improve students’ academic literacy. The program involved several stages: pretest, material delivery, workshops, group discussions, writing assistance, result presentations, and posttest. The results showed a significant improvement in students' understanding, evidenced by a 30-point increase in posttest scores. Additionally, participants' enthusiasm and positive feedback from both students and teachers indicated that the activity was relevant and beneficial. This program is expected to contribute to fostering a scientific writing culture among high school students.